Radio man the remarkable rise and fall of C.O. Stanley - Frankland, Mark 1934-2012 (Institution of Engineering and Technology, 2002)
Radio Man tells the story of C.O. Stanley, the unconventional Irishman who acquired Pye Radio at the beginning of the broadcasting age. Though he started with little experience and even less money, he was to make Pye a major player in the British electronics industry - only to crash it spectacularly forty years later. This revealing and meticulously researched text is written within the broad context of the political, technological and business changes of the time, and shows how a very ambitious businessman was brought down by the qualities that made him so successful.